The summer wind [large type] - Monroe, Mary Alice (Monroe, Mary Alice. Lowcountry summer trilogy., 2014)
A grandmother about to move to a retirement home invites her three grown granddaughters to her historic house on Sullivan's Island for one more summer together. There they must all find a way to weather both a tropical storm and the stressful changes in their lives.